Marché des capitaux, Intermédiaire financier et la croissance économique : Revue de littérature - MSATFA Zouheir; KHOMSI Houda (African Scientific Journal, 2025)
Abstract: The role of finance, primarily embodied by financial intermediaries and capital markets, occupies a central place in current debates on economic growth. However, there is still ambiguity regarding the most favorable structure to stimulate this growth. Some schools of thought, such as those of McKinnon and Shaw (1973), argue that a banking-dominated financial system is more conducive to economic growth. Others, like Paudel (2005), emphasize the advantages of stock markets, particularly their liquidity, which allows companies to quickly access the necessary capital. This paper aims to shed light on this controversy by relying on a thorough theoretical analysis and a review of the existing literature, covering various spatio-temporal perspectives. First, the study focuses on the relationship between finance and economic growth. It then explores the financial structures most favorable to growth, highlighting the mechanisms through which finance contributes to stimulating the economy. Keywords: Capital market, financial intermediaries, economic growth, impact Résumé : Le rôle de la finance, incarné principalement par les intermédiaires financiers et les marchés des capitaux, occupe une place centrale dans les débats actuels sur la croissance économique. Cependant, une ambiguïté persiste quant à la structure la plus favorable pour stimuler cette croissance. Certains courants, comme ceux de McKinnon et Shaw (1973), soutiennent qu’un système financier dominé par les banques est plus propice à la croissance économique. D’autres, à l’instar de Paudel (2005), mettent en avant les avantages des marchés boursiers, notamment leur liquidité, qui permet aux entreprises d’accéder rapidement aux capitaux nécessaires. Ce travail a pour objectif d’éclairer cette controverse en s’appuyant sur une analyse théorique approfondie et une revue de la littérature existante, couvrant diverses perspectives spatio-temporelles. Dans un premier temps, l’étude se concentre sur la relation entre la finance et la croissance économique. Ensuite, elle explore les structures financières les plus favorables à la croissance, en mettant en lumière les mécanismes par lesquels la finance contribue à dynamiser l’économie. Mots clés : Marché des capitaux, intermédiaires financiers, Croissance économique, impact.